Recent advances in oil-repellent surfaces. (17th February 2016) - Milionis, A.; Bayer, I. S.; Loth, E.
Abstract : During the last years, emerging research has focused on the development and design of novel materials that can successfully repel oils and other liquids. In order to achieve such properties, different fabrication strategies can be followed. Up to now, several reviews have been published that focus and investigate each of these concepts individually without giving an entire overview of all the existing approaches for achieving oil-repellency. In this review pertaining to advances and developments since 2011, we summarise progress on fabrication, design and understanding of all the existing concepts for obtaining materials that are oil-repellent including smooth oleophobic materials, textured superoleophobic and superomniphobic surfaces, and lubricated porous/textured substrates. In each of these categories, we highlight the most successful methods to produce oil-repellent surfaces while their applications are also demonstrated. Finally, recent studies and new trends focusing on the development of oil-repellent materials by following more environmentally friendly routes such as the use of short-chain or even no perfluorinated compounds, but also fabrication methods that do not involve the use of hazardous or flammable solvents, are also discussed.